Electric field distribution and initial jet motion induced by spinneret configuration for molecular orientation in electrospun fibers. (January 2018) - Li, Xiang; Lin, Jinyou; Zeng, Yongchun
Graphical abstract: The needle spinneret creates a non-uniform electric field with an extremely high electric field strength concentrated on the needle outlet while the hole spinneret creates a relatively uniform electric field from the spinneret to collector, which enables the needle spinneret to form a stable jet more rapidly and to create a higher initial jet velocity in comparison to the hole spinneret, bringing about a higher degree of molecular orientation in resultant fibers. Highlights: We explore electric field for fiber thining and molecular orientation during process. Electric field distribution and jet motion are induced by spinneret configuration. Jet motion further explains the molecular orientation in fibers from two spinnerets. Electric field around the spinneret outlet determines molecular orientation in fiber. Abstract: Understanding the molecular orientation of electrospun fibers is a key challenge for tailoring fiber properties. The studies of electric field distribution, and the motion of the initial portion of the polymer jet, are of interest for clarifying molecular orientation in fibers during electrospinning. In this work, we study the impact of electric field distribution and the initial jet motion induced by two kinds of spinneret configurations, referred to as a needle configuration and a hole configuration, on molecular orientation in electrospun PEO fibers. Using FE-SEM, FTIR and WAXD techniques, the fiber diameter and molecular orientation of the fibers prepared with the needle electrospinning system and the hole electrospinning system are characterized. To explore jet stretching and chain orientation during the spinning process, electric field simulation and high-speed photography are performed to obtain the electric field characteristics and to measure the initial jet velocities for the needle and the hole systems. Our results reveal the higher electric field strength around the spinneret and the larger initial jet velocities, which depend on the spinneret configuration, result in the higher degree of molecular orientation in fibers.